ANALYSIS OF STUDENTS' ERROR IN COMPLETING MATHEMATICS PROBLEMS ON CIRCLE MATERIALS WITH THE WATSON CATEGORY - Buulolo , Derman (Afore : Jurnal Pendidikan Matematika, 2022)
This study aims to describe students' mistakes in solving math problems on circle material and how the factors that cause errors in solving problems on circle material. This study uses qualitative research with a descriptive approach. The informants of this study were 22 grade VIII students of SMP Negeri 2 Amandraya. Data collection techniques used were written tests and interviews. The results of this study indicate various types of errors caused by: (i) incorrect data, students are unable to identify the data provided, (ii) procedures are incorrect, students miscalculate or enter values ​​incorrectly, (iii) missing data, incomplete input data and principles or formulas used are incorrect, (iv) conclusions are lost, students do not write down the final results of the work, (v) conflict level response, students lack maximum readiness in solving questions, (vi) indirect completion, problem solving process from each stage that has illogical reasons, (vii) high skill problems, errors in calculations and errors in changing algebraic forms, (viii) other than the seventh category above, students do not write down answers or do not answer at all.